INSTRUMEN REKOMENDASI DPRD DALAM PENYELENGGARAAN KEWENANGAN PERIJINAN OLEH PEMERINTAH DAERAH - Made Jayantara (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
Recommendation of the Local House of Representative (DPRD) is a common administrativeinstitution employed in the local government decision making process. However, thisinstitution does not recognized by the law. Hence, its presence dan used in the processof decision of public license contains various problem, such as: (1) its status under theadministrative law; (2) its implication to the validity of the license; (3) and the positionof the head of the local government, the degree of the local government responsibility asthe recommendation receiver and the DPRD as the recommendation giver to the negativeimpact of the license. These facts resulted in needs for conducting research for clarifyingthe status, measuring the implication of the recommendation over the validity of the license,and the range of responsibility head of the local government and the DPRD to the impact ofthe license.This research is focused into two issues, namely: (1) how is the position and function ofthe DPRD in the process of issuing of license; and (2) how would be the implication ofthe DPRD’s recommendation over the range of responsibility of the head of the localgovernment and DPRD in the issuing of license. This research is limited to the practice ofissuing of recommendation in the Local Government Province of Bali.This research shallemploy normative approach and uses both primary and secondary legal resources.The research resulted in two inventions: firstly, recommendation of DPRD is not recognizedby the law in the level of province local government neither it’s the authorithy of the DPRDon supervising the governor. The recommendation recognized by law is the recommendationas an administrative legal instrument in the performance of local government by thegovernor, particularly for performing the function of decision making or the conductingof governmental act. Hence, recommendation of DPRD is a state custom in performingstate governmental function. Secondly, recommendation has two functions, namely: acondition and confirmation. In the function of condition, recommendation is a prerequisitefor adopting public decision. In the function of confirmation, recommendation is a merely anexpression of an agreement provided by a certain instution for adopting a public decision.Recommendation in the function of condition, binds the recommendation giver to bearresponsibility over the result of the implementation of the decision. While, in the functionof confirmation the giver may not necessarily responsible to the result of the performanceof the decision. However, under the principle of good faith, the giver is under obligationto bear responsibility over the result of the implementation of the decision whenever therecommendation is given under a bad faith.